Effect of Stigma on HIV/Aids Orphaned Children in Nabiganda Town Council Butaleja District - Eseza Bashihwendera (Uganda Christian University, 2024)
This research study was guided by the topic Effect of stigma on HIV/AIDS orphaned children in Nabiganda Town Council, Butaleja district. It was guided by the following research objectives: To assess effect of labeling and discrimination on HIV/AIDS orphaned children in Nabiganda Town council in Butaleja District, to find out the effect of stereotyping on education among HIV/AIDS orphaned children in Nabiganda Town council in Butaleja District and lastly to examine the relationship between stigma and Nutrition among HIV/AIDS orphaned children in Nabiganda Town council in Butaleja District. The study was guided by three research questions. This study used both a quantitative and qualitative research design and it considered a population of 100 participants which arose at a sample size of 80 respondents. The study used descriptive statics where mean standard deviation and graphs were used in the study. The study findings revealed that: Numerous risk factors contribute to HIV/AIDs poor levels such as labeling and discrimination, that HIV/AIDS discrimination is directed towards families and uninfected children as a result of stigmatization at home, that paternal bereavement leads to stigmatization of HIV orphaned children regardless of their own HIV status in addition to this, revealed that stereotyping has an impact on education of HIV orphaned children, that HIV/AIDS stereotyping affects educational wellbeing of HIV orphaned children in terms of enrolment, that stereotyping consequently diminishes orphaned children‟s morale for attendance, that stereotyping limits access to resources of HIV/orphaned children in addition to this findings also revealed that: Stereotyping has an impact on education of HIV orphaned children, that HIV/AIDS stereotyping affects educational wellbeing of HIV orphaned children in terms of enrolment that poor nutrition accounts for increased disease burden among HIV/AIDS children under the age of five. The study recommended that: There should be more investments by different Governments in a number of strategies to ensure that HIV stigmatization is reduced in different communities and lastly that there is need for the to sensitize the community and people taking care of HIV affected children to always have proper meals that can help ensure that they avoid diseases.